Soil fertility status of coconut and arecanut growing soils - Vasundhara, R.; Prakash, N. B.; Anil Kumar, K. S.; Hegde , Rajendra; Dharumarajan, S. (Journal of Plantation Crops, 2021)
The present study was undertaken to assess the soil fertility status of major coconut and arecanut growing soils in different agro-climatic conditions of Karnataka. Based on the agro-climate variability, thirty typical soil pedons representing five different agro-climatic zones (ACZs) of Karnataka, namely, eastern dry zone (EDZ), southern dry zone (SDZ), southern transitional zone (STZ), hilly zone (HZ), and coastal zone (CZ) were studied for their physicochemical properties. The study revealed that soils of semi-arid (EDZ and SDZ) and sub-humid (STZ) zones have near neutral to moderately alkaline reaction and humid region soils (coastal and hilly zones) have high acidity. The soils are non-saline with low cation exchange capacity. Greater soil organic carbon was recorded in arecanut soils than coconut under all ACZs except coastal zone. The major nutrients status of the soil samples indicated that the available nitrogen is low in all the pedons; the pooled data of available nitrogen content was higher in arecanut (166.3 kg ha-1) than coconut (152.6 kg ha-1), and hilly zone soils recorded higher available nitrogen. A wide range of available P2O5 was noticed in coconut and arecanut soils, ranging from 1.0 to 64.2 kg ha-1. The coconut soils (11.5 kg ha-1) recorded higher available P2O5 than arecanut soils (9.62 kg ha-1) when data were pooled. The soils were low to medium in available potassium, and a higher available K2O content was recorded in arecanut soils (151.7 kg ha-1) compared to coconut (110.1 kg ha-1). The available K2O ranged from 66.8 to 511.7 kg ha-1 in the surface and 37.6 to 461.2 kg ha-1 in sub-surface soils.